Superconducting Precursors in Bi/Pb Multiphase Cuprates Fabricated by the Solar Technology and their Comparative Study by Torque Magnetometry Methods - Mamniashvili, Grigor Ivan; Donadze, Giorgi; Tavkhelidze, Valery; Gulamova, Dilbar (Engineering, Technology & Applied Science Research, 2023)
A special method has been applied to synthesize HTSC samples of Bi1.7Pb0.3Sr2Ca(n-1)CunOy with increased local inhomogeneities, using solar energy for the melting and following superfast quenching of the melt (SFAQ-T technology). This study carried out a comparative analysis using low-frequency torsional vibration and resonant vibrating reed spectroscopy methods. The results showed a possibility for the existence of high-temperature superconducting precursors with Tc = 107-138 K and the potential advantages of the application of the resonant vibrating reed method.